La confidence radiophonique: entre effacement du je et revendication du moi - Horlacher, Anne-Sylvie (My University, 2004)
In this study, we investigate speakers' involvement in their own discourse. The data consist of Radio "Phone-In" Confidential Chat in conversational French discourse. These telephone conversations evolve around subjectmatters that are in many ways taboo. Therefore, we will first see how participants manage to speak about these subjects. We will analyse exemples in which participants take a distance with regard to the stories they are telling, using linguistic means such as impersonal constructions or the pronoun "on" in order to avoid implication in the discourse (this strategy corresponds to the concept of modulation in Vion's terminology). We will also examine confidences in which participants clearly stand behind what they say, using many personal pronouns and especially the recurrent form "moi je" (this would account for tension according to Vion). We will then try to explain the emergence of such forms in our data, where decency and restraint generally prevail over subjectivity. We will conclude by arguing that "on" and "moi je" respond to the participants'need for deletion on the one hand and publicity on the other, allowing them to establish themselves as different from others, and thus unique.